Association of functional polymorphisms of matrix metalloproteinase (MMP)‐1 and MMP‐3 genes with colorectal cancer - Hinoda, Yuji; Okayama, Naoko; Takano, Naofumi; Fujimura, Kozue; Suehiro, Yutaka; Hamanaka, Yuichiro; Hazama, Shoichi; Kitamura, Yutaka; Kamatani, Naoyuki; Oka, Masaaki (International journal of cancer, 2002)
Matrix metalloproteinase (MMP)‐1 and MMP‐3 genes are associated with tumor cell invasion and metastasis with their promoter polymorphisms influencing the level of transcription. Our study explored the association of these polymorphisms with colorectal cancer risk in a Japanese population. DNA was extracted from peripheral blood of 101 patients with colorectal cancer and 127 age‐ and gender‐matched healthy volunteers. Genotyping was carried out using PCR‐RFLP and direct sequencing. In the MMP‐1 gene polymorphism, the frequency of the 2G/2G genotype that is associated with higher enzyme activity was significantly increased in colorectal cancer patients when compared to controls (p = 0.0067; OR = 2.077; 95% CI = 1.221–3.534). With regard to the MMP‐3 polymorphism, unexpectedly, the frequency of the 6A/6A genotype causing lower enzyme activity was significantly increased in patients (p = 0.0129; OR = 2.110; 95% CI = 1.165–3.822). Because the loci for the 2 MMP genes are closely linked, we examined linkage disequilibrium between the 2 loci using expectation‐maximization algorithm. We found that the 2 loci were in linkage disequilibrium and that 2G‐6A haplotype was significantly increased in patients compared to controls (p = 0.0010; OR = 1.949; 95% CI = 1.305–2.911). Our present data suggest that the MMP‐1 and MMP‐3 promoter polymorphisms may be associated with a colorectal cancer susceptibility in Japanese. © 2002 Wiley‐Liss, Inc.